Formation of a Treatment Algorhythm for Snake Bite Envenomation in Turkey - Okur, Mehmet Ihsan; Yildirim, Alpagan Mustafa; Ince, Bilsev (Ortadogu Ad Pres & Publ Co, 2012)
Objective: Despite many publications about snakebite envenomation in Turkey, no standardized treatment suggestions have been made. Antivenom treatment seems to be inappropriate in the majority of publications. In general, only one vial antivenom is administered to most patients even if they had serious poisoning symptoms. The aim of the present study was to establish a follow-up and treatment algorhytm depending on the experience acquired from 43 cases. Material and Methods: Forty-three patients (16 female and 27 male) who suffered from snake poisoning between 2006 and 2009 were followed-up and treated within the current study. Patients were hospitalized for an average of 4.92 days. Patients were administered snake antivenom and medical treatment. Surgical intervention was performed when necessary. Results: The first approach was to give a 0.25 mg subcutaneous epinephrine injection on the arm. Following that, an average of 5.81 (2-17) vials of antiserum was administered. Five patients with hemoglobin levels decreased below 10 g/dL received a total of 12 units of blood. A previously fasciotomized leg of a patient was grafted. Another patient's second finger was amputated. A patient with a necrotized finger underwent debridement and groin flap operation. No patient underwent fasciotomy. Three patients had INR elevation, and thrombocytopenia developed in two patients. These patients recovered without specific treatment. The remaining patients recovered smoothly with medical treatment. Conclusion: An algorhytm was developed depending on follow-up and treatment methods used for the patients throughout the present study. A successful outcome with low complication rate can be achieved using the presented algorhytm in case of venomous snakebite.
Türkiye'de yılan isırmalarına ba?lı zehirlenmede tedavi algoritması oluşturulması
Keywords: Snake bites; poisoning; Turkey; algorithms